Variability in traditional processing of gari: A major food security product from cassava - Bechoff, Aurélie; Tomlins, Keith I.; Chijoke, Ugo; Ilona, Paul; Bennett, Ben; Westby, Andrew; Boy, Erick (Practical Action Publishing, 2019)
Cassava is a major crop for food security in Nigeria and its principal processed form is gari. Gari processing practices were observed in the south-west (Oyo State) and south-east (Benue State) of Nigeria using two complementary approaches: 1) semi-quantitative surveys with processors (n = 123); and 2) actual detailed measurements at processing units (n = 7). Size of processing operations and types of practices differed significantly between the two states. There were also intra-state differences, influenced by ethnicity and customs. Variability of processing practices should be considered while seeking to improve processing productivity and introducing nutritious varieties of cassava to feed the fast-growing Nigerian population.